Concealed, Unobtrusive Ear-Centered EEG Acquisition: cEEGrids for Transparent EEG - Bleichner, Martin G.; Debener, Stefan (Frontiers in Human Neuroscience, 2017)
Electroencephalography (EEG) is an important clinical tool and frequently used to study the brain-behavior relationship in humans noninvasively. Traditionally, EEG signals are recorded by distributing electrodes on the scalp and keeping them in place with glue, rubber bands, or elastic caps. This setup provides good coverage of the head, but is impractical for EEG acquisition in natural daily-life situations. Here we propose the transparent EEG concept. Transparent EEG aims for motion tolerant, highly portable, unobtrusive and near invisible data acquisition with minimum disturbance of a user’s daily activities. In recent years several ear-centered EEG solutions that are compatible with the transparent EEG concept have been presented. We discuss work showing that miniature electrodes placed in and around the human ear are a feasible solution, as they are sensitive to pick up electrical signals stemming from various brain and non-brain sources. We also describe the cEEGrid flex-printed sensor array, which enables unobtrusive multi-channel EEG acquisition from around the ear. In a number of validation studies we found that the cEEGrid enables the recording of meaningful continuous EEG, event-related potentials and neural oscillations. Here we explain the rationale underlying the cEEGrid ear-EEG solution, present possible use cases and identify and open issues that need to be solved on the way towards transparent EEG.